2010
DOI: 10.3109/00365521003710190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-resolution transabdominal ultrasound in the diagnosis of complications of Crohn's disease

Abstract: High-resolution transabdominal ultrasound done by experienced examiners has an excellent diagnostic accuracy in the diagnosis of complications in patients with Crohn's disease. Thus, it can be recommended as one of the primary investigative procedures for evaluation of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…39,40 MRI is a noninvasive, radiationsparing tool but its diagnostic accuracy in detecting SB strictures has not been assessed since no study has compared MRI findings with surgery, except for a promising report referring only to five patients. 36 Despite diagnosis with TUS of CD SB strictures being the object of several reports, 8,9,10,30,[41][42][43] a single study 8 used as reference standard only the surgical pathological findings, showing an excellent sensitivity (100%) and specificity (91%) in the detection of at least one stricture in patients submitted to surgery for obstructive symptoms. The present study confirms that TUS has a high sensitivity (87%) and specificity (100%) in the assessment of the presence of at least one stricture in patients with obstructive symptoms (data not shown), but in addition it shows that SICUS has a higher diagnostic accuracy than TUS to detect: 1) the presence of more than two strictures; 2) those located in the proximal tract of SB; 3) extension of strictures, independently from the presence of prestenotic dilatation and of obstructive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 MRI is a noninvasive, radiationsparing tool but its diagnostic accuracy in detecting SB strictures has not been assessed since no study has compared MRI findings with surgery, except for a promising report referring only to five patients. 36 Despite diagnosis with TUS of CD SB strictures being the object of several reports, 8,9,10,30,[41][42][43] a single study 8 used as reference standard only the surgical pathological findings, showing an excellent sensitivity (100%) and specificity (91%) in the detection of at least one stricture in patients submitted to surgery for obstructive symptoms. The present study confirms that TUS has a high sensitivity (87%) and specificity (100%) in the assessment of the presence of at least one stricture in patients with obstructive symptoms (data not shown), but in addition it shows that SICUS has a higher diagnostic accuracy than TUS to detect: 1) the presence of more than two strictures; 2) those located in the proximal tract of SB; 3) extension of strictures, independently from the presence of prestenotic dilatation and of obstructive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,28 Ten studies including a total of 1011 patients with established CD were identified. 10,11,[16][17][18][27][28][29][30][31] Two studies were performed in pediatric populations. 16,30 Eight studies used surgical specimens as reference standard.…”
Section: Detection Of Stricturesmentioning
confidence: 99%
“…The highest values were registered for the detection of abscesses (sensitivity 90-100%, specificity 92-99%, PPV 90% and NPV 99% [49,58]. Therefore, US plays a pivotal role in the detection of abscesses, even though it can produce false positive results [57].…”
Section: Crohn's Diseasementioning
confidence: 96%
“…It is well known that intestinal US has high sensitivity and specificity both for the primary diagnosis of CD [45][46][47][48], and for detecting complications such as stenosis, fistulas and abscesses [25,45,49]. The global sensitivity of intestinal US for the primary diagnosis of CD has been assessed within many meta-analyses, showing a good diagnostic accuracy.…”
Section: Crohn's Diseasementioning
confidence: 99%
See 1 more Smart Citation